Chinese-Style Decentralization and Health System Reform - Hipgrave, David; Guo, Sufang; Mu, Yan; Guo, Yan; Yan, Fei (Public Library of Science, 2015)
April 2012 marked the end of the three years China set for implementation of the first phase of its health system reform (HSR), and several recent reports assessed progress in this massive undertaking. Two of them identify impressive achievements in health insurance coverage, infrastructure development, and uptake of services, but all three reports draw attention to slow progress in several areas: quality of services at the community level, persisting financial risk for individuals, and the almost complete lack of independent tracking of progress in health outcomes. The reports also recommend an increased focus on burgeoning rates of non-communicable diseases. Government-commissioned external reviews also highlighted these and other issues, underscoring related high-level awareness. However, none of the reports attempted to place China's HSR in the context of the nation's evolving political economy, or to predict its influence on achievement of the major HSR objective—equitable and affordable access to quality health services.